2004
DOI: 10.1115/1.2008970
|View full text |Cite
|
Sign up to set email alerts
|

Flow Mechanism for Stall Margin Improvement due to Circumferential Casing Grooves on Axial Compressors

Abstract: A computational study is carried out to understand the physical mechanism responsible for the improvement in stall margin of an axial flow rotor due to the circumferential casing grooves. Computational fluid dynamics simulations show an increase in operating range of the low speed rotor in the presence of casing grooves. A budget of the axial momentum equation is carried out at the rotor casing in the tip gap in order to understand the physical process behind this stall margin improvement. It is shown that for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…Numerous techniques including stepped tip gaps and passive casing treatments such as circumferential grooves and skewed axial slots have been reported in open literature [5][6][7]. Such profiled wall treatments have usually benefited compressor stability at the cost of compressor efficiency.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous techniques including stepped tip gaps and passive casing treatments such as circumferential grooves and skewed axial slots have been reported in open literature [5][6][7]. Such profiled wall treatments have usually benefited compressor stability at the cost of compressor efficiency.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, this is yet another proof that injecting fluid into the low-momentum tip flows, responsible for up to 30% of aerodynamic losses in axial compressors [51], will have an effect on compressor operational stability. If this effect is positive, the increase of axial momentum close to the tip can also have a positive impact on the stall margin of the downstream stages [75], [76] as well as the current stage.…”
Section: Change In the Axial Momentum Of Tip Flows Due To Water Injecmentioning
confidence: 99%
“…The unsteadiness and shock motion were studied experimentally and numerically by Copenhaver et al [9], whose study indicated the presence of deterministic unsteadiness near the location of the shock. Some approaches to controlling the tip leakage flow and improving the compressor stability, known as casing treatment, used slots and grooves placed in the shroud over the tip of the blade [10][11][12][13]. Recirculation casing treatment employs a passageway to remove high-pressure fluid from downstream of the rotor leading or trailing edge and inject it upstream of the point of removal [14][15][16].…”
Section: Introductionmentioning
confidence: 99%